2019
DOI: 10.1186/s12917-019-2222-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ovarian steroids on vascular endothelial growth factor a expression in bovine uterine endothelial cells during adenomyosis

Abstract: BackgroundAdenomyosis is a uterine dysfunction defined as the presence of endometrial glands within the myometrium. There is evidence that proangiogenic factors may play a role during the development of adenomyosis; however, exact mechanism remains unknown. The aim of the study was to determine the action of vascular endothelial growth factor A (VEGFA) in uterine tissue and uterine vascular endothelial cells during adenomyosis.ResultsUterine tissues were collected and examined for the presence and extent of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 48 publications
0
9
0
1
Order By: Relevance
“…Thus, the endometrium of endometriosis patients might be hyper-responsive to estrogen stimulation and thus enhance the expression of VEGF. In addition, the dysregulation of VEGFRs (downregulation of VEGFR-1 and upregulation of VEGFR-2) seems to be responsible for endometriosis [ 114 ]. Kim et al have shown that expression of VEGFR-1, VEGFR-2, and VEGFR-3 was higher in the mid-luteal endometrium of patients with endometriosis [ 115 ].…”
Section: Vegf In Reproductive Failurementioning
confidence: 99%
“…Thus, the endometrium of endometriosis patients might be hyper-responsive to estrogen stimulation and thus enhance the expression of VEGF. In addition, the dysregulation of VEGFRs (downregulation of VEGFR-1 and upregulation of VEGFR-2) seems to be responsible for endometriosis [ 114 ]. Kim et al have shown that expression of VEGFR-1, VEGFR-2, and VEGFR-3 was higher in the mid-luteal endometrium of patients with endometriosis [ 115 ].…”
Section: Vegf In Reproductive Failurementioning
confidence: 99%
“…The rabbit ovary and uterus undergo substantial transformation following ovulation [ 4 ]. The endometrium undergoes morphological and physiological cyclic changes, including proliferation, differentiation, apoptosis, and regeneration [ 11 , 12 ]. Therefore, angiogenesis, which is the development of new vasculature from preexistent vessels, plays a fundamental role in tissue remodeling and is necessary for implantation and normal pregnancy and proper uterine blood supply maintenance [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the reproductive cycle, both estrogen and progesterone hormones play a crucial role in controlling the uterine cyclic changes and functions of their receptors. Furthermore, these hormones influence the uterine vasculature growth either directly through their receptors or indirectly by initiating proangiogenic factor release, including vascular endothelial growth factor (VEGF) [12,15]. VEGF is one of the most common angiogenic factors that stimulate robust angiogenesis, increases blood vessel permeability, and plays a crucial role in ovarian folliculogensis and consequently CL formation and maintenance [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Нині інформація про внутрішньоутробний розвиток сечостатевої системи визначається теорією Мюллера, визнаною більшістю дослідників [14,21,33,36,40].…”
Section: результати обговоренняunclassified